2004
DOI: 10.1007/s00467-004-1497-x
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid pharmacokinetics and growth retardation in children with renal transplants

Abstract: Long-term glucocorticoid treatment contributes to the growth retardation in children after renal transplantation. We investigated whether determination of prednisone (PN) and prednisolone (PL) in plasma and PN, PL, and 6-beta-hydroxyprednisolone (betaOH-PL) in urine could help to predict growth. PN and PL pharmacokinetics were studied in 36 children, from 5 to 15 years of age, receiving daily (D) or alternate-day (AD) oral PN treatment. Statural growth velocity was evaluated over a 1-year period. We compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Whereas, Chavatte et al [14] attributed that corticosteroid therapy is probably the main factor inducing stunted growth in pediatric renal transplant recipients. Meanwhile, abnormalities of growth hormone/insulin-like growth factor (IGF) axis have been reported in children with CRF and post transplant and thought to contribute to poor growth [15].…”
Section: Discussionmentioning
confidence: 97%
“…Whereas, Chavatte et al [14] attributed that corticosteroid therapy is probably the main factor inducing stunted growth in pediatric renal transplant recipients. Meanwhile, abnormalities of growth hormone/insulin-like growth factor (IGF) axis have been reported in children with CRF and post transplant and thought to contribute to poor growth [15].…”
Section: Discussionmentioning
confidence: 97%
“…[15][16][17] Seikku and associates and Sarna and associates 18,19 demonstrated that the area under the serum concentration-time curve of methylprednisolone, rather than dosage-was related to growth inhibition in pediatric liver and renal transplant recipients. However, Chavatte and associates 20 reported that pharmacokinetics studies of prednisone and prednisolone were not predictive of growth retardation in children with RTx. In our study, all but 2 patients were on low-dose daily steroid treatment (2 to 7 mg/m 2 /d) and pharmacokinetics studies of prednisolone or methylprednisolone were not available.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced allograft function has been considered a risk factor for growth impairment after renal TX in children (20,27,28). In a previous study from our center, GC exposure, rather than dose, was related to adrenal suppression and growth retardation in pediatric TX patients (9).…”
Section: Discussionmentioning
confidence: 99%
“…The higher S-MP and GBA values observed in the obese patients in the present study may be partially explained by reduced clearance of MP (8), thus suggesting dosing of MP according to ideal body weight or body surface area. Pharmacokinetic parameters have been reported to relate to the immunosuppressive efficacy (7,18) and to clinical side effects (9,19) of GCs, although with one contradiction (20). To investigate the GC milieu in pediatric TX patients receiving chronic GC therapy, we used two different analytical methods and correlated the results with the adverse effects of MP.…”
Section: Discussionmentioning
confidence: 99%